Sociophysics Analysis of the Dynamics of Peoples' Interests in Society - Ishii, Akira; Kawahata, Yasuko (Frontiers in Physics, 2018)
As a method of analyzing and predicting social phenomena using social media as data, we present analyses based on the mathematical model of the hit phenomenon, which is one of the theories of sociophysics. The transition of the number of social media posts for movies, music concerts, and a YouTube movie are explained, using the mathematical model of the hit phenomenon. For entertainment topics, the direct communication strength, D, indicates the satisfaction of the current fans or supporters, whereas the indirect communication strength, P, indicates the power to acquire a new support layer. Thus, this is effective not only for the analysis of entertainment and marketing strategy but also for burst analysis on the social media.